Targeting CD38 and PD-1 with isatuximab plus cemiplimab in patients with advanced solid malignancies: results from a phase I/II open-label, multicenter study. Issue 1 (20th January 2022) - Zucali, Paolo Andrea; Lin, Chia-Chi; Carthon, Bradley C; Bauer, Todd M; Tucci, Marcello; Italiano, Antoine; Iacovelli, Roberto; Su, Wu-Chou; Massard, Christophe; Saleh, Mansoor; Daniele, Gennaro; Greystoke, Alastair; et al.
Abstract : Background: Preclinical data suggest that concurrent treatment of anti-CD38 and antiprogrammed death 1 (PD-1)/programmed death ligand 1 (PD-L1) antibodies substantially reduce primary tumor growth by reversing T-cell exhaustion and thus enhancing anti-PD-1/PD-L1 efficacy. Methods: This phase I/II study enrolled patients with metastatic castration-resistant prostate cancer (mCRPC) or advanced non-small cell lung cancer (NSCLC). The primary objectives of phase I were to investigate the safety and tolerability of isatuximab (anti-CD38 monoclonal antibody)+cemiplimab (anti-PD-1 monoclonal antibody, Isa+Cemi) in patients with mCRPC (naïve to anti-PD-1/PD-L1 therapy) or NSCLC (progressed on anti-PD-1/PD-L1-containing therapy). Phase II used Simon's two-stage design with response rate as the primary endpoint. An interim analysis was planned after the first 24 (mCRPC) and 20 (NSCLC) patients receiving Isa+Cemi were enrolled in phase II. Safety, immunogenicity, pharmacokinetics, pharmacodynamics, and antitumor activity were assessed, including CD38, PD-L1, and tumor-infiltrating lymphocytes in the tumor microenvironment (TME), and peripheral immune cell phenotyping. Results: Isa+Cemi demonstrated a manageable safety profile with no new safety signals. All patients experienced ≥1 treatment-emergent adverse event. Grade≥3 events occurred in 13 (54.2%) patients with mCRPC and 12 (60.0%) patients with NSCLC. Based on PCWG3 criteria, assessment of best overall response with Isa+Cemi in mCRPC revealed no complete responses (CRs), one (4.2%) unconfirmed partial response (PR), and five (20.8%) patients with stable disease (SD). Per RECIST V.1.1, patients with NSCLC receiving Isa+Cemi achieved no CR or PR, and 13 (65%) achieved SD. In post-therapy biopsies obtained from patients with mCRPC or NSCLC, Isa+Cemi treatment resulted in a reduction in median CD38+ tumor-infiltrating immune cells from 40% to 3%, with no consistent modulation of PD-L1 on tumor cells or T regulatory cells in the TME. The combination triggered a significant increase in peripheral activated and cytolytic T cells but, interestingly, decreased natural killer cells. Conclusions: The present study suggests that CD38 and PD-1 modulation by Isa+Cemi has a manageable safety profile, reduces CD38+ immune cells in the TME, and activates peripheral T cells; however, such CD38 inhibition was not associated with significant antitumor activity. A lack of efficacy was observed in these small cohorts of patients with mCRPC or NSCLC. Trial registration numbers: NCT03367819 .